The Effectiveness of Platelet-Rich Plasma in the Treatment of Tendinopathy: A Meta-analysis of Randomized Controlled Clinical Trials. (January 2017) - Fitzpatrick, Jane; Bulsara, Max; Zheng, Ming H.
Background: Tendinopathy is very common in the general population. There are increasing numbers of clinical studies referring to platelet-rich plasma (PRP) and platelet-poor plasma (PPP) as treatments for tendinopathy. Purpose: To perform a meta-analysis of the outcomes of the PRP groups by preparation method and injection technique in tendinopathy. To determine the clinical effectiveness of the preparations and to evaluate the effect of controls used in the studies reviewed. Study Design: Systematic review and meta-analysis. Methods: The PubMed, EMBASE, CINAHL, and Medline databases were searched in March 2012, April 2014, and August 2015, and randomized controlled trials using autologous blood, PRP, PPP, or autologous conditioned plasma in tendinopathy with outcome measures of pain and follow-up time of 3 months were included in this review. Trials including surgery, tendon tears, and muscle or ligament injuries were excluded. Study quality was assessed using the Cochrane Collaboration risk-of-bias tool by 2 reviewers. Data were pooled using random-effects meta-analysis. The primary outcome measure was a change in pain intensity. Where more than 1 pain scale was included, a functional score was selected ahead of a visual analog scale score. Results: A total of 18 studies (1066 participants) were included. Eight studies were deemed to be at low risk of bias. The most significant outcomes in the PRP groups were seen in those treated with highly cellular leukocyte-rich PRP (LR-PRP) preparations: GPS kit (standardized mean difference [SMD], 35.75; 95% CI, 28.40-43.10), MyCells kit (SMD, 31.84; 95% CI, 17.56-46.13), Prosys kit (SMD, 42.99; 95% CI, 37.73-48.25), and unspecified LR-PRP (SMD, 34.62; 95% CI, 31.69-37.55). When the LR-PRP system types were grouped, there was a strongly positive effect (SMD, 36.38; 95% CI, 34.00-38.77) when compared with leukocyte-poor PRP (SMD, 26.77; 95% CI, 18.31-35.22). In assessing the control groups, there was no clear difference between different types of control injections: saline (SMD, 14.62; 95% CI, 10.74-18.50), local anesthetic (SMD, 15.00; 95% CI, 7.66-22.34), corticosteroid (SMD, 23.82; 95% CI, 10.74-18.50), or dry needling (SMD, 25.22; 95% CI, 21.27-29.16). Conclusion: There is good evidence to support the use of a single injection of LR-PRP under ultrasound guidance in tendinopathy. Both the preparation and intratendinous injection technique of PRP appear to be of great clinical significance.